Gen Z and the second-hand paradox : Understanding overconsumption in the digital age of fashion - Vellamo, Aida (My University, 2026)
Second-hand fashion has become an increasingly central part of contemporary fashion consumption, often framed as an alternative response to the unsustainable and overconsumptive nature of fast fashion. At the same time, recent public discourse suggests that the contemporary forms of second-hand consumption may also enable and normalise overconsumption, particularly among younger consumers. The aim of this thesis is to examine how overconsumption is constructed, maintained, and perceived in the context of online second-hand fashion consumption among Generation Z. The thesis addresses this aim by examining how overconsumptive behaviour is constructed and maintained in contemporary online second-hand fashion, with a particular focus on Generation Z consumers and how they navigate competing values in excessive second-hand consumption. Together, these perspectives form the basis for answering the main research question of how Generation Z consumers perceive overconsumption in the context of online second-hand fashion. The study adopts a qualitative research approach grounded in netnographic methods. The empirical material consists of publicly available TikTok haul videos related to excessive online second-hand fashion and their associated comment sections. This approach enables the examination of consumption practices and the views associated with them as they naturally appear in digital environments. The data is analysed using qualitative thematic analysis which, together with the theoretical framework, enables the formation of a comprehensive understanding of overconsumption in second-hand fashion among this generation. The findings indicate that overconsumptive behaviour in the context of second-hand clothing is not only acknowledged but also openly displayed and socially accepted. Platform affordances such as ease of purchasing and a wide product selection, combined with the central role of social media in the everyday lives of Generation Z together reinforce frequent and high levels of consumption. In addition, central values of Generation Z, as well as psychological mechanisms typically associated with fast fashion, such as cognitive dissonance and moral compensation, were clearly present in the context of second-hand clothing. Sustainability is notably absent from the analysed content, suggesting that second-hand consumption is often treated as morally acceptable by default rather than actively reflected upon. Overall, the thesis contributes to research on sustainable fashion consumption and contemporary consumer behaviour by offering an emerging perspective on overconsumption within online second-hand markets. By focusing on Generation Z and naturally occurring social media data, the study highlights the need to critically reassess sustainability assumptions surrounding online second-hand fashion and the platforms that enable and shape second-hand consumption.

Käytettyjen vaatteiden (second hand) suosio muodissa on kasvanut merkittäväksi osaksi nykyaikaista muodin kulutusta, ja sitä pidetään usein vaihtoehtona pikamuodin kestämättömälle ja ylikulutusta ruokkivalle luonteelle. Viimeaikainen julkinen keskustelu on kuitenkin tuonut esiin huolen siitä, että käytettyjen vaatteiden kulutuksen nykyiset, erityisesti digitaaliset muodot saattavat myös mahdollistaa ja normalisoida ylikulutusta etenkin nuorten kuluttajien keskuudessa. Tämä kehitys on ristiriidassa käytettyjen vaatteiden ympäristöllisesti vastuullisena pidetyn luonteen kanssa. Tämä pro gradu -tutkielma tarkastelee, miten käytetyn muodin ylikulutus rakentuu, miten sitä ylläpidetään digitaalisilla alustoilla ja miten se koetaan Z-sukupolven keskuudessa. Tutkimus keskittyy Z-sukupolveen ostovoimaltaan kasvavana kuluttajajoukkona sekä siihen, miten he tasapainoilevat keskenään ristiriitaisten arvojen välillä käytettyjen vaatteiden kulutuksessa. Näiden pohjalta tutkimus pyrkii vastaamaan päätutkimuskysymykseen: miten Z-sukupolven edustajat kokevat ylikulutuksen käytetyn muodin kontekstissa? Tutkimus toteutettiin laadullisena tutkimuksena, joka perustui netnografisiin menetelmiin. Empiirinen aineisto koostui julkisesti saatavilla olevista TikTokissa julkaistuista käytettyjen vaatteiden ostosten esittelyvideoista sekä niihin liittyvistä kommenttikentistä. Tämä lähestymistapa mahdollisti kulutuskäytäntöjen ja niihin liittyvien näkemysten tarkastelun sellaisina kuin ne luonnollisesti digitaalisissa ympäristöissä ilmenevät. Aineisto analysoitiin laadullisen temaattisen analyysin avulla, muodostaen yhdessä teoreettisen viitekehyksen kanssa kattavan kokonaiskuvan käytetyn muodin ylikulutuksesta sukupolven keskuudessa. Tulokset osoittavat, että ylikulutuksellinen käyttäytyminen käytettyjen vaatteiden kontekstissa on paitsi tiedostettua myös avointa ja sosiaalisesti hyväksyttyä. Alustojen tarjoamat mahdollisuudet, kuten ostamisen helppous ja laaja valikoima, yhdistyvät sosiaalisen median keskeiseen rooliin Z-sukupolven arjessa ja vahvistavat yhdessä tiheää ja runsasta kulutusta. Lisäksi Z-sukupolvelle keskeiset arvot sekä tyypillisesti pikamuotiin liitetyt psykologiset mekanismit, kuten kognitiivinen dissonanssi ja moraalinen kompensointi, olivat selkeästi havaittavissa myös käytettyjen vaatteiden kontekstissa. Kestävyysnäkökulma oli analysoidussa sisällössä huomattavan vähäisessä roolissa, mikä viittaa siihen, että käytettyjen vaatteiden kulutusta pidetään usein lähtökohtaisesti moraalisesti hyväksyttävänä ilman aktiivista pohdintaa. Tutkielma täydentää kestävän muodin kulutusta ja nykyaikaista kuluttajakäyttäytymistä koskevaa tutkimusta tarjoamalla uuden, ylikulutukseen liittyvän näkökulman käytettyjen vaatteiden myyntialustoihin. Tutkimuksen tulokset korostavat tarvetta arvioida kriittisesti käytettyyn muotiin liitettyjä kestävyysolettamuksia sekä niitä digitaalisia alustoja, jotka mahdollistavat ja muovaavat nykyaikaista käytettyjen vaatteiden kulutusta ja sen suuntaa.
Keywords: overconsumption; Gen Z; consumer behaviour; second-hand; online retail; TikTok; fashion consumption; retail industry; sustainable consumption; circular economy; ylikulutus; Z-sukupolvi; kuluttajakäyttäytyminen; second hand; verkkokauppa; kirppari; käytetty muoti; kestävä kulutus; kiertotalous